Attitudes of Lower Saxony and North Rhine-Westphalia Teachers to Bilingual Geography Lessons - Kuckuck, Miriam; Steinmeier, Laurenz (Journal of Geography Education, 2018)
Bilingual subject teaching enjoys increasing popularity at more and more schools, regardless of the type of school and grade. Especially Geography is taught widely as a bilingual subject. In the context of bilingual subject teaching, the concept CLIL (Content and Language Integrated Learning) is well established by now. Despite the high number of research-based and conceptual suggestions concerning bilingual Geography teaching, few of the studies focus on teachers as their objects of investigation. This paper aims to address this desideratum and to answer the following research questions: What are teachers' general attitudes towards bilingual subject teaching? Which opportunities and challenges of bilingual Geography teaching do they see and which didactic strategies and principles for good bilingual Geography teaching do they use in their lessons? To answer these research questions, a total of 103 teachers from the states of Lower Saxony and North Rhine-Westphalia participated in an online survey. The results show that the colleagues teaching Geography bilingually evaluate the teaching more positively than their colleagues solely teaching Geography in German. Moreover, language learning in addition to the subject-related learning represents both an opportunity and a challenge. The strategies used are based primarily on Geography lessons taught in German.
Keywords: bilingual Geography teaching, CLIL, opportunities and challenges, teacher survey, attitudes